PENANAMAN NILAI-NILAI TOLERANSI PADA PEMBELAJARAN PPKN DALAM MENGATASI DISKRIMINASI PADA SISWA SMP NEGERI 3 SINJAI KAB. SINJAI: tindakan penelitian pada siswa di sekolah - Nurul Azizah; Andi Sugiati; Indah Ainun Mutiara (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The changing times require learning strategies that instill tolerance to prevent discriminatory behavior among students. This study aims to examine students’ understanding of tolerance values, describe Civics (PPKn) learning strategies that foster tolerance, analyze the effectiveness of these strategies in addressing discrimination, and identify supporting and inhibiting factors in their implementation at SMP Negeri 3 Sinjai, Sinjai Regency. A descriptive qualitative method was employed, with data collected through observation, interviews, questionnaires, and documentation. Data were analyzed through reduction, display, and conclusion drawing with verification. The research results show that: 1) students understand the values of tolerance, although some still require guidance to apply them more consistently; 2) PPKn learning strategies such as group discussions, case studies, daily stories, and cooperation are effective in instilling the value of tolerance; 3) the effectiveness of these strategies is evident from changes in student behavior, reinforced by the acknowledgment of teachers, homeroom teachers, and students; 4) the success of these strategies is supported by a conducive classroom atmosphere, adequate facilities, the role of teachers, and school support, but is hindered by differences in student character and external environmental influences.